2016
DOI: 10.1002/jor.23382
|View full text |Cite
|
Sign up to set email alerts
|

The initial repair response of articular cartilage after mechanically induced damage

Abstract: The regenerative potential of articular cartilage (AC) defects is limited and depends on defect size, biomechanical conditions, and age. Early events after overloading might be predictive for cartilage degeneration in the long term. Therefore, the present aim is to investigate the temporal response of cartilage to overloading at cell, matrix, and tissue level during the first period after mechanical overloading. In the present study, the effect of high loading (∼8 MPa) at a high rate (∼14 MPa/s) at day 0 durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Our model is also purely biomechanical, for instance, it does not take into account potential cytokine release due to injury/overloading and subsequent PG loss, or possible repair mechanisms of PGs . These mechanisms would be potential improvements which could be incorporated into the current method if the parameters (biomechanical, biological) were known.…”
Section: Discussionmentioning
confidence: 99%
“…Our model is also purely biomechanical, for instance, it does not take into account potential cytokine release due to injury/overloading and subsequent PG loss, or possible repair mechanisms of PGs . These mechanisms would be potential improvements which could be incorporated into the current method if the parameters (biomechanical, biological) were known.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to consider that the generation of the lesion disrupts cartilage ECM and that can cause lost of PGs and collagens, as we could observe by immunostaining. Other limitations of this study may be the lost of PGs because of the culture [ 64 ], time of culture and the absence of mechanical stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, ex vivo incubation systems are vastly improving, as it has been shown that cartilage‐on‐bone explants can stay intact for up to 8 weeks . These explants can also be compressed and biochemically supplemented as required, and are thus increasingly resembling the in vivo environment . Such systems may in time provide an opportunity to omit short‐term animal studies (see overlap between explant incubation time and in vivo studies in Fig.…”
Section: Comparison Between In Vitro and In Vivo Overloading Studiesmentioning
confidence: 99%